German guidelines on screening, diagnosis and treatment of alcohol use disorders - Mann, Karl (European addiction research, 2017)
Evidence-based strategies for screening, diagnosing and treating alcohol use disorders (AUD) are instrumental in the early and better management of individuals at risk for or suffering from AUD. However, existing guidelines vary and may be biased by conflicts of interests. Unbiased recommendations can be achieved only if sufficient detail is provided on the composition and representativeness of author groups, methodological rigor, handling of potential conflicts of interest and financing. This paper presents the first evidence-based guidelines for AUD from German-speaking countries. These guidelines are based on the work of delegates from a representative sample of 46 scientific societies (mostly medical) from Austria, Germany and Switzerland dealing with AUD. It also included patients and relatives. Recommendations were derived from a standardised hierarchical process involving quality controls drawn from existing guidelines, de novo literature searches and/or expert experience. Potential conflicts of interest were assessed yearly and led to exclusion from voting in specific areas. An overall cost of more than 400,000€ (for alcohol and tobacco guidelines) were exclusively covered by the participating societies and academic institutions. More than 100 recommendations on screening, diagnostics and treatment of AUD are outlined in this paper, and their scientific background is given in the online supplementary material. Tables of aggregated study synopses (in English) and the full version of guidelines (in German) are available (see “Links”).
Gesehen am 09.04.2018